Model Selection Analysis of 600/1 067 mm Gauge Changeable Bogie - LIU Xiaoyan; HUANG Yunhua; ZHANG Lixin; ZHANG Lijun; XU Hongjiang (机车电传动)
By comparing the existing gauge changeable technology abroad, the type selection analysis and scheme determination of each component of 600/1 067 mm gauge changeable bogie were carried out. The rail-changing mode of 600/1 067 mm gauge changeable bogie was determined, and the structural scheme and the rail-changing process of each component of 600/1 067 mm gauge changeable bogie were determined.